Recent changes in MBBS curriculum in psychiatry in Bangladesh: a call for attention - Roy, Susmita; Arafat, SM Yasir (Bangladesh Journal of Psychiatry, 2020)
Abstract not available Bang J Psychiatry 2018;32(2): 24-25